High baseline soluble urokinase plasminogen activator receptor (suPAR) serum levels indicate adverse outcome after resection of pancreatic adenocarcinoma - Loosen, Sven; Bergmann, Frank; Longerich, Thomas (Carcinogenesis, 2019)
We show that elevated levels of circulating suPAR in patients with resectable pancreatic adenocarcinoma are associated with a significantly impaired overall sur
Gesehen am 04.12.2019